Lithium-containing compound / carbon composite material and preparation method and application thereof
By using lithium-containing compound/carbon composite materials as lithium-replenishing additives in lithium-ion batteries, the problems of low lithium-replenishing capacity, poor stability, and poor matching in the existing technology are solved, and high energy density and good electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411659116.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-24
AI Technical Summary
The existing lithium compensation additives have problems such as low lithium supplement capacity, poor stability, and poor battery matching in lithium-ion batteries, which limit the increase in the energy density of lithium-ion batteries.
By mixing the hybrid carbon material with the reducing lithium-containing solution for in-situ reaction, a lithium-containing compound/carbon composite material is generated. The lithium-containing compound is evenly distributed on the carbon substrate using chemical bonds to form a compact composite structure.
The high -supplement lithium capacity, good air stability and battery matching, improved the energy density of lithium -ion batteries, reduced the generation of by -products, and simplified the process process.
Smart Images

Figure CN119361659A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy materials, and in particular to a lithium-containing compound / carbon composite material and a preparation method and application thereof. Background Art
[0002] At present, with the rapid development of electric vehicles and the widespread application of large-scale energy storage technology, new energy technologies have been vigorously developed. Among them, lithium-ion batteries have many advantages such as high energy density, high power density, and long cycle life, and occupy an important position in the field of energy storage technology. However, during the first charge and discharge process of lithium-ion batteries, the electrolyte decomposes at the negative electrode interface, resulting in irreversible lithium loss, resulting in a decrease in the capacity and energy density of lithium-ion batteries, which limits its further development.
[0003] In response to this problem, many lithium replenishment methods have been proposed and vigorously developed. At present, compared with the negative electrode lithium replenishment technology, the positive electrode lithium replenishment technology has always been the direction pursued by the industry due to its advantages such as high air stability and compatibility with industrialization. The positive electrode lithium compensation method is a technology to improve the energy density of lithium-ion batteries. It introduces lithium-containing active materials with high lithium ion capacity into the positive electrode to compensate for the irreversible loss of active lithium in the negative electrode during the first charging process, thereby improving the energy density of lithium-ion batteries. The positive electrode lithium replenishment additives currently studied mainly include lithium-rich compounds, nanocomposites based on conversion reactions, and binary lithium compounds. However, these materials have some challenges and disadvantages in practical applications. First, these positive electrode lithium replenishment additives usually face the problem of poor environmental stability, especially in electrolytes. For example, lithium-rich compounds such as Li2O, Li2O2, and Li3N have high theoretical capacities, but in practical applications, their stability and compatibility with electrolytes limit their application. In addition, these materials may leave inactive substances such as metal oxides, fluorides, and sulfides after the first lithium replenishment, and these residues may reduce the energy density of the battery. Secondly, the compatibility of positive electrode lithium supplement additives with existing battery processes is also a challenge. Some lithium supplement materials may require additional process steps or special production environments, which may increase the cost and complexity of battery manufacturing. In addition, positive electrode lithium supplement additives may affect other electrochemical properties of the battery, such as reversible capacity, cycle stability, and rate performance. To overcome these challenges, researchers are exploring new materials and methods to improve the performance and compatibility of positive electrode lithium supplement additives. Summary of the invention
[0004] The purpose of the present invention is to provide a lithium-containing compound / carbon composite material and a preparation method and application thereof, so as to solve the technical problems of low lithium supplement capacity, poor stability and poor battery matching of existing lithium compensation additives.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a lithium-containing compound / carbon composite material, comprising the following steps:
[0007] The hybrid carbon material and the reducing lithium-containing solution are mixed and reacted in situ to obtain a lithium-containing compound / carbon composite material;
[0008] The lithium-containing compound generated by the in-situ reaction is tightly compounded with the carbon substrate through chemical bonds and is evenly distributed on the carbon substrate.
[0009] Furthermore, the hybrid carbon material contains a hybrid element and a carbon material, and the hybrid carbon material is obtained by performing a hybrid reaction on the carbon material, and the hybrid element and the carbon material are bonded by chemical bonds;
[0010] The concentration of the hybrid carbon material in the reducing lithium-containing solution is 0.01-1 g / mL.
[0011] Furthermore, the hybrid element accounts for 1 to 99% of the mass of the hybrid carbon material;
[0012] The chemical bond between the hybrid element and the carbon material includes NC, OC, SC, PC, Co-C or Mo-C.
[0013] Further, the carbon material comprises one or more of graphite, graphene, expanded graphite, carbon nanotubes, MXene, carbon black, carbon fiber, Ketjen black, activated carbon, porous carbon, hard carbon, soft carbon and graphyne;
[0014] The hybrid element includes one or more of N, O, S, P, Co, Mo, Fe, Ni, Mn, V, La, Nb, W and Al elements.
[0015] Furthermore, the temperature of the in-situ reaction is 30 to 200° C., and the time of the in-situ reaction is 1 to 10 hours;
[0016] The hybridization reaction comprises one of a vapor deposition method, a hydrothermal method, and a high-energy ball milling method.
[0017] Furthermore, the reducing lithium-containing solution comprises a reducing lithium-containing solution A and a reducing lithium-containing solution B, the reducing lithium-containing solution A contains reducing lithium and a solvent, the reducing lithium comprises one or more of naphthalene lithium, biphenyl lithium and anthracene lithium, and the solvent comprises one or more of tetrahydrofuran, ethylene glycol dimethyl ether and toluene.
[0018] Furthermore, the concentration of the reducing lithium-containing solution A is 0.01 to 10 mol / L;
[0019] The reducing lithium-containing solution B is a mixture of lithium powder and a lithium salt-containing electrolyte.
[0020] Further, the lithium-containing compound comprises one or more of lithium nitride, lithium oxide, lithium sulfide and lithium phosphide;
[0021] The chemical bond between the lithium-containing compound and the carbon substrate includes one or more of CSP-Li, C-Co-O-Li, C-Mo-N-Li, CN-Mo-Li, CO-Ni-Li, CO-Li, CN-Li, CS-Li, CP-Li, C-Co-Li and C-Mo-Li.
[0022] The invention also provides a lithium-containing compound / carbon composite material.
[0023] The present invention also provides an application of a lithium-containing compound / carbon composite material in lithium compensation of a lithium battery positive electrode material.
[0024] Beneficial effects of the present invention:
[0025] (1) The present invention can control the preparation of lithium-containing compounds / carbon composite materials. Elements are loaded on various carbon substrates by gas phase / liquid phase / solid phase methods, and the operation methods are diverse. The loaded elements are divided into two categories, one is the elements that are pre-connected with the carbon material, and the other is the precursor elements that are subsequently chemically lithiated with a reducing lithium-containing solution to provide active lithium. The electrochemical activity of the lithium supplement can be effectively regulated by the components and proportions of the connector and the catalyst element. By regulating the reaction conditions (such as temperature, stirring rate, etc.) during the lithiation of the hybrid carbon material, the particle size of the lithium supplement (lithium-containing compound) obtained after the precursor element is lithiated can be effectively regulated, thereby accurately and controllably regulating its electrochemical activity.
[0026] (2) The lithium supplement agent obtained by the one-step method of the present invention has the advantage of stable properties. Since the lithium-containing compound is formed in situ in the carbon material structure, it is effectively coated by the carbon material and thus has good air stability.
[0027] (3) The lithium supplement of the present invention has a high specific capacity. Since the lithium-containing compound component generated by the in-situ reaction is uniformly distributed in the form of nanoparticles and tightly bound to the carbon material substrate, it has high reactivity, can reduce the decomposition platform and improve the decomposition efficiency. Moreover, compared with the common ball milling of the lithium supplement and the carbon material, since the lithium supplement is in close contact with the carbon substrate, it has good conductivity and can ensure its electrochemical activity during the electrochemical charging process (common lithium supplements will produce inert products after decomposition, resulting in reduced conductivity and decreased kinetics).
[0028] (4) The lithium supplement of the present invention has few by-products. Due to good kinetics, the lithium supplement can be fully decomposed. And the amount of catalyst can be greatly reduced, further reducing the residue. As for the inevitable residue, since it is tightly combined with the carbon material, it will always be locked on the carbon substrate and will not be dispersed in the electrode to have a side effect on the electrode kinetics.
[0029] (5) The present invention has the advantages of simple operation, good product uniformity and easy industrialization due to the solution lithiation method. It has the advantages of simple process, low production cost and good lithium compensation effect, and can be applied to various carbon-based materials and various alkali metal batteries to compensate for the corresponding active material loss. The reaction product prepared by the preparation method of the present invention is easy to separate from the solution, and the separated solvent can be recycled, which has the advantage of being green and environmentally friendly.
[0030] In summary, the present invention can prepare a lithium-containing compound / carbon composite material through a simple chemical method, which has a high lithium replenishment capacity and can be used as a lithium compensation additive material for lithium-ion batteries to compensate for the lithium loss at the negative terminal of the lithium-ion battery, thereby improving the energy density of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a transmission electron microscope image of lithium phosphide / lithium sulfide / carbon composite material;
[0032] Figure 2 It is a schematic diagram of the structure of lithium phosphide / lithium sulfide / carbon composite material;
[0033] Figure 3 The first charge and discharge curve of chemically lithiated lithium phosphide / lithium sulfide / carbon composite material;
[0034] Figure 4 The first cycle charge and discharge curves of the half-cell of the lithium cobalt oxide positive electrode sheet without and with the lithium phosphide / lithium sulfide / carbon composite material;
[0035] Figure 5 The half-cell cycle capacity curve of the lithium cobalt oxide positive electrode sheet containing lithium phosphide / lithium sulfide / carbon composite material;
[0036] Figure 6 This is a scanning electron microscope image of a lithium oxide / cobalt / carbon composite material;
[0037] Figure 7 The first cycle charge and discharge curves of half-cells of nickel cobalt manganese oxide positive electrode sheets without and with lithium oxide / cobalt / carbon composite materials;
[0038] Figure 8 The half-cell cycle capacity curve of the positive electrode sheet of nickel cobalt manganese oxide containing lithium oxide / cobalt / carbon composite material;
[0039] Fig. 9The first cycle charge and discharge curve of a soft-pack full battery assembled with a lithium nickel cobalt manganese oxide positive electrode and a silicon carbon negative electrode containing a lithium nitride / molybdenum / carbon composite material;
[0040] Fig.10 Cycling capacity curve of a soft-pack full-cell assembled with a lithium nickel cobalt manganese oxide cathode containing a lithium nitride / molybdenum / carbon composite material and a silicon-carbon anode;
[0041] Fig.11 Schematic diagram of the structure of lithium-containing compound / carbon composite material. DETAILED DESCRIPTION
[0042] The present invention provides a method for preparing a lithium-containing compound / carbon composite material, comprising the following steps:
[0043] The hybrid carbon material and the reducing lithium-containing solution are mixed and reacted in situ to obtain a lithium-containing compound / carbon composite material;
[0044] The lithium-containing compound generated by the in-situ reaction is tightly compounded with the carbon substrate through chemical bonds and is evenly distributed on the carbon substrate.
[0045] In the present invention, the hybrid carbon material comprises a hybrid element and a carbon material, and the hybrid carbon material is obtained by subjecting the carbon material to a hybrid reaction, wherein the hybrid element and the carbon material are bonded via chemical bonds;
[0046] The concentration of the hybrid carbon material in the reducing lithium-containing solution is 0.01 to 1 g / mL, preferably 0.02 to 0.8 g / mL, more preferably 0.1 to 0.6 g / mL, and even more preferably 0.2 to 0.5 g / mL.
[0047] In the present invention, the hybrid element accounts for 1 to 99% of the mass of the hybrid carbon material, preferably 5 to 90%, more preferably 10 to 80%, and more preferably 20 to 70%;
[0048] The chemical bond between the hybrid element and the carbon material includes NC, OC, SC, PC, Co-C or Mo-C.
[0049] In the present invention, the carbon material comprises one or more of graphite, graphene, expanded graphite, carbon nanotubes, MXene, carbon black, carbon fiber, Ketjen black, activated carbon, porous carbon, hard carbon, soft carbon and graphyne, preferably one or more of graphite, graphene, expanded graphite, carbon nanotubes, MXene, carbon black, carbon fiber, Ketjen black and hard carbon.
[0050] In the present invention, the hybrid element comprises one or more of N, O, S, P, Co, Mo, Fe, Ni, Mn, V, La, Nb, W and Al elements, preferably one or more of N, O, S, P, Co, Mo, Fe, Ni, Mn, V, La and Nb elements.
[0051] In the present invention, the temperature of the in-situ reaction is 30-200°C, preferably 35-150°C, more preferably 50-100°C, and more preferably 55-80°C; the time of the in-situ reaction is 1-10h, preferably 2-8h, and more preferably 5-6h.
[0052] In the present invention, the hybridization reaction is preferably one of a vapor deposition method, a hydrothermal method, and a high-energy ball milling method.
[0053] In the present invention, the reducing lithium-containing solution comprises a reducing lithium-containing solution A and a reducing lithium-containing solution B, wherein the reducing lithium-containing solution A contains reducing lithium and a solvent, wherein the reducing lithium comprises one or more of naphthalene lithium, biphenyl lithium and anthracene lithium, preferably anthracene lithium; and the solvent comprises one or more of tetrahydrofuran, ethylene glycol dimethyl ether and toluene, preferably tetrahydrofuran.
[0054] In the present invention, the concentration of the reducing lithium-containing solution A is 0.01 to 10 mol / L, preferably 1 to 9 mol / L, and more preferably 2 to 8 mol / L.
[0055] In the present invention, the reducing lithium-containing solution B is a mixture of lithium powder and a lithium salt-containing electrolyte, and the concentration of the lithium powder in the reducing lithium-containing solution B is 0.01 to 10 mol / L, preferably 1 to 9 mol / L, and more preferably 2 to 8 mol / L.
[0056] In the present invention, the lithium-containing compound comprises one or more of lithium nitride, lithium oxide, lithium sulfide and lithium phosphide, preferably one or more of lithium nitride, lithium sulfide and lithium phosphide.
[0057] In the present invention, the chemical bond between the lithium-containing compound and the carbon substrate is preferably one or more of CSP-Li, C-Co-O-Li, C-Mo-N-Li, CN-Mo-Li, CO-Ni-Li, CO-Li, CN-Li, CS-Li, CP-Li, C-Co-Li and C-Mo-Li.
[0058] The invention also provides a lithium-containing compound / carbon composite material.
[0059] The present invention also provides an application of a lithium-containing compound / carbon composite material in lithium compensation of a lithium battery positive electrode material.
[0060] In the present invention, during the lithium compensation of the lithium battery positive electrode material, functional additives can be added to the lithium-containing compound / carbon composite material to regulate the electrochemical activity of the composite material, further modify the lithium-containing compound / carbon composite material, and improve the interface stability; the functional additives include one or more of silane coupling agent, thiourea, polyacrylic acid, polyvinylidene fluoride, polyethylene glycol and polyethylene oxide.
[0061] In the present invention, the lithium-containing compound / carbon composite material is used for lithium compensation of positive electrode materials, and its initial charging specific capacity is 300 to 1000 mAh / g.
[0062] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0063] Example 1
[0064] The graphene was finely milled by high-energy mechanical ball milling at 300r for 2h to obtain a particle size, and sulfur and phosphorus were loaded in the treated graphene in sequence by gas phase method, with the loading amounts being 1wt% and 40wt%, respectively. At 35°C, the sulfur- and phosphorus-loaded graphene was added to a 1mol / L naphthalene lithium solution, with the content of the sulfur- and phosphorus-loaded graphene being 0.5g / mL, and stirred for 5h, washed with tetrahydrofuran, and dried to obtain a tightly compounded Li3P / Li2S / C composite material, which can be used as a lithium compensation additive for the positive electrode of lithium-ion batteries.
[0065] The Li3P / Li2S / C composite material was made into an electrode, assembled with metal lithium into a half-cell, and its electrochemical performance was tested. It was further added as an additive (5wt%) to the lithium cobalt oxide positive electrode as a lithium supplement additive, assembled with metal lithium into a half-cell, and its electrochemical performance was tested.
[0066] Figure 1 This is a transmission electron microscope image of the Li3P / Li2S / C composite material prepared in Example 1 constructed according to the present invention. From the image, it can be seen that the crystalline lithium compound is evenly and densely distributed on the carbon surface. Therefore, it can be obtained that the chemical lithiation method successfully prepares the Li3P / Li2S / C composite material on the surface of the carbon material, and the crystalline Li3P is evenly distributed on the carbon substrate.
[0067] Figure 2This is a schematic diagram of the structure of the Li3P / Li2S / C composite material. Due to the good affinity between sulfur molecules and carbon, they can be evenly distributed on the surface of the carbon material to form a sulfur-carbon material. Phosphorus is further evaporated on the sulfur-carbon material. Due to the good affinity between sulfur and phosphorus, phosphorus-sulfur bonds can be formed, which promotes the uniform distribution of phosphorus on the carbon material. In the subsequent lithiation process, the evenly distributed phosphorus can be evenly lithiated to form lithium phosphide, and the in-situ grown lithium phosphide is evenly distributed on the carbon material and tightly combined. This structure helps to fully decompose lithium phosphide and improve the delithiation capacity.
[0068] Figure 3 The charge and discharge capacity diagram of the Li3P / Li2S / C composite material prepared in Example 1 constructed according to the present invention, with a charge cut-off voltage of 3.5V (vs. Li + / Li), the charging capacity can reach 780mAh / g at a current of 10mA / g.
[0069] Figure 4 The first cycle charge and discharge capacity comparison diagram of the lithium cobalt oxide positive electrode of the Li3P / Li2S / C composite material prepared in Example 1 constructed according to the present invention. It can be seen from the figure that when the charge cut-off voltage is 4.5V (vs. Li + / Li), the lithium cobalt oxide positive electrode material was charged at a rate current of 0.1C (1C = 150mAh / g). When 5wt% Li3P / Li2S / C composite material was added, the first charging capacity of the lithium cobalt oxide positive electrode was increased by 25mAh / g, indicating that the Li3P / Li2S / C composite material is helpful to improve the first charging lithium ion capacity of the lithium cobalt oxide battery, and can make up for the lithium ion consumption on the negative electrode surface during the first charging and discharging process of the lithium ion battery, thereby improving the energy density of the lithium ion battery.
[0070] Figure 5 This is a cycle performance diagram of the Li3P / Li2S / C composite material prepared in Example 1 constructed according to the present invention added to the lithium cobalt oxide positive electrode material. It can be seen from the figure that at a current of 1C, the charge and discharge performance of the lithium cobalt oxide positive electrode material is basically not attenuated after 40 cycles, indicating that the addition of the lithium compensator will not have a negative impact on the cycle stability of the positive electrode material.
[0071] Example 2
[0072] The cobalt element was loaded into hard carbon by hydrothermal method, with a loading amount of 50wt%. After drying, the hard carbon loaded with Co was placed in a tubular furnace and oxidized with oxygen to obtain a Co3O4 / C composite material. At 50°C, the Co3O4 / C composite material was added to a 2mol / L biphenyl lithium solution, with a content of 1g / mL of the Co3O4 / C composite material, and stirred for 10h, washed with tetrahydrofuran, and dried to obtain a Li2O / C / Co composite material, which can be used as a lithium compensation additive for the positive electrode of lithium-ion batteries.
[0073] Li2O / C / Co composite (5 wt%) was added as an additive to lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2) as a lithium supplement additive in the positive electrode and assembled with metallic lithium into a half-cell, and its electrochemical performance was tested.
[0074] Figure 6 This is a scanning electron microscope image of the Li2O / C / Co composite material prepared in Example 2 constructed according to the present invention. It can be seen from the figure that there are a large number of nanoparticles on the surface of the carbon material, which are evenly distributed. Therefore, it can be concluded that the chemical lithiation method successfully prepares the Li2O / C / Co composite material on the surface of the carbon material, and the nanoparticles are evenly distributed on the carbon substrate.
[0075] Figure 7 The first cycle charge and discharge capacity comparison diagram of the positive electrode of nickel cobalt manganese oxide of the Li2O / C / Co composite material prepared in Example 2 constructed according to the present invention. It can be seen from the figure that when the charge cut-off voltage is 4.5V (vs. Li + / Li), the nickel cobalt manganese oxide positive electrode material was charged at a rate current of 0.1C (1C = 200mAh / g). When 5wt% Li2O / C / Co composite material was added, the first charging capacity of the nickel cobalt manganese oxide positive electrode was increased by 25mAh / g, indicating that the Li2O / C / Co composite material is helpful to improve the first charging lithium ion capacity of the nickel cobalt manganese oxide battery, and can make up for the lithium ion consumption on the negative electrode surface during the first charging and discharging process of the lithium ion battery, thereby improving the energy density of the lithium ion battery.
[0076] Figure 8 This is a cycle performance diagram of the Li2S / Li3P / C composite material prepared in Example 1 constructed according to the present invention added to the nickel cobalt manganese oxide positive electrode material. It can be seen from the figure that at a current of 0.5C, the charge and discharge performance of the nickel cobalt manganese oxide positive electrode material is basically not attenuated after 100 cycles, indicating that the addition of the lithium compensator will not have a negative impact on the cycle stability of the positive electrode material.
[0077] Example 3
[0078] Molybdenum was loaded into carbon nanotubes by ball milling, with a loading amount of 1wt%. Mo-loaded carbon nanotubes were nitrided by gas phase method. Mo / C / N was added into 1mol / L electrolyte containing active lithium powder at 100℃, with a Mo / C / N content of 0.3g / mL. After being stirred for 1h, the mixture was washed with ethylene glycol dimethyl ether, and the mixture was heated to 180℃ and dried to obtain Li3N / Mo / C composite material, which can be used as lithium compensation additive for positive electrode of lithium ion battery.
[0079] Li3N / Mo / C composite material (5wt%) was added to the nickel cobalt manganese oxide lithium positive electrode as a lithium supplement additive, and assembled with a high specific capacity silicon carbon negative electrode into a soft-pack full battery, and its electrochemical performance was tested.
[0080] Fig. 9 The first cycle charge and discharge capacity comparison chart of the soft-pack full battery assembled with the Li3N / Mo / C composite material prepared in Example 3 of the present invention as a lithium supplement additive and the nickel cobalt manganese oxide positive electrode matched with the silicon carbon negative electrode. It can be seen from the figure that when the charging cut-off voltage is 4.3V (vs. Li + / Li), the full battery was charged at a rate current of 0.1C (1C = 200mAh / g). When 5wt% Li3N / Mo / C composite material was added, the first charging capacity of the nickel cobalt manganese oxide lithium positive electrode increased by 35mAh / g, indicating that the Li3N / Mo / C composite material is helpful to improve the first charging lithium ion capacity of the nickel cobalt manganese oxide lithium battery, and can make up for the lithium ion consumption on the negative electrode surface during the first charging and discharging process of the lithium ion battery, thereby improving the energy density of the lithium ion battery. Fig.10 This is the cycle performance diagram of the soft-pack full battery. It can be seen from the figure that at a current of 0.5C, the reversible capacity of the soft-pack full battery with the lithium supplement increased by 50 mAh g -1 After 100 cycles, the capacity retention rate is still 85%, indicating that the lithium supplement can increase the cycle stability of the soft-pack full battery on the basis of improving the capacity of the soft-pack full battery.
[0081] Example 4
[0082] Molybdenum, vanadium, niobium, tungsten and aluminum were loaded in MXene by hydrothermal method, with the loading amount of 0.1wt% respectively, and these substances were used as high entropy catalysts. Further, at 200°C, nickel, cobalt, manganese, iron and sulfur were loaded in MXene containing high entropy catalyst by high energy ball milling method, with the loading amount of 1wt%, 1wt%, 1wt%, 1wt% and 20wt% respectively, and the substance was used as high entropy lithium supplementation precursor. The MXene loaded with high entropy catalyst and high entropy lithium supplementation precursor was further oxidized by gas phase method. At 55°C, the composite was added to a 1mol / L naphthalene lithium solution, and the content of the composite was 0.1g / mL. After being fully stirred for 10h, it was washed with ethylene glycol dimethyl ether, and the mixture was dried to obtain a high entropy Li2O / Li2S / C / Ni / Co / Mn / Fe composite material, which can be used as a lithium compensation additive for the positive electrode of lithium ion batteries.
[0083] Example 5
[0084] Molybdenum is loaded on carbon fiber, vanadium is loaded on carbon nanotubes, niobium is loaded on graphene, tungsten is loaded on hard carbon, and aluminum is loaded on activated carbon by hydrothermal method, and the loading amount is 0.1wt%. The carbon materials loaded with the above active components are mixed in equal mass ratio to obtain a high entropy conductive agent, and nickel, cobalt, manganese, phosphorus, and sulfur are loaded in the high entropy conductive agent by ball milling method, and the loading amount of each single component is 10wt%. The material obtained by ball milling is used as a high entropy lithium supplement precursor. The high entropy lithium supplement precursor is added to a 8mol / L lithium powder / electrolyte (1M LiTFSI in DME) solution, and the ratio of the high entropy lithium supplement precursor in the lithium powder / electrolyte solution is 0.1g / mL. The high entropy lithium supplement precursor is ball milled at 200℃ for 10h to obtain a high entropy Li3P / Li2S / C / Ni / Co / Mn composite material, which can be used as a lithium compensation additive for the positive electrode of lithium-ion batteries.
[0085] As can be seen from the above embodiments, the present invention provides a lithium-containing compound / carbon composite material and its preparation method and application. The present invention optimizes the components of the composite lithium supplement agent, and the corresponding composite lithium supplement agent (i.e., lithium-containing compound / carbon composite material) can be used as a novel lithium compensation additive for lithium ion positive electrodes to compensate for the loss of active lithium at the negative electrode, thereby improving the capacity and energy density of the battery.
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a lithium-containing compound / carbon composite material, characterized in that: The following steps are involved: The hybrid carbon material and the reducing lithium-containing solution are mixed and reacted in situ to obtain a lithium-containing compound / carbon composite material; The lithium-containing compound generated by the in-situ reaction is tightly compounded with the carbon substrate through chemical bonds and is evenly distributed on the carbon substrate.
2. The method for preparing the lithium-containing compound / carbon composite material according to claim 1, characterized in that: The hybrid carbon material comprises a hybrid element and a carbon material, wherein the hybrid carbon material is obtained by subjecting the carbon material to a hybrid reaction, and the hybrid element and the carbon material are bonded via chemical bonds; The concentration of the hybrid carbon material in the reducing lithium-containing solution is 0.01-1 g / mL.
3. The method for preparing the lithium-containing compound / carbon composite material according to claim 2, characterized in that: The hybrid element accounts for 1 to 99% of the mass of the hybrid carbon material; The chemical bond between the hybrid element and the carbon material includes NC, OC, SC, PC, Co-C or Mo-C.
4. The method for preparing the lithium-containing compound / carbon composite material according to claim 2 or 3, characterized in that: The carbon material comprises one or more of graphite, graphene, expanded graphite, carbon nanotubes, MXene, carbon black, carbon fiber, Ketjen black, activated carbon, porous carbon, hard carbon, soft carbon and graphyne; The hybrid element includes one or more of N, O, S, P, Co, Mo, Fe, Ni, Mn, V, La, Nb, W and Al elements.
5. The method for preparing the lithium-containing compound / carbon composite material according to claim 2 or 3, characterized in that: The temperature of the in-situ reaction is 30 to 200° C., and the time of the in-situ reaction is 1 to 10 hours; The hybridization reaction comprises one of a vapor deposition method, a hydrothermal method, and a high-energy ball milling method.
6. The method for preparing the lithium-containing compound / carbon composite material according to any one of claims 1 to 3, characterized in that: The reducing lithium-containing solution comprises a reducing lithium-containing solution A and a reducing lithium-containing solution B, wherein the reducing lithium-containing solution A contains reducing lithium and a solvent, wherein the reducing lithium comprises one or more of naphthalene lithium, biphenyl lithium and anthracene lithium, and the solvent comprises one or more of tetrahydrofuran, ethylene glycol dimethyl ether and toluene.
7. The method for preparing the lithium-containing compound / carbon composite material according to claim 6, characterized in that: The concentration of the reducing lithium-containing solution A is 0.01 to 10 mol / L; The reducing lithium-containing solution B is a mixture of lithium powder and a lithium salt-containing electrolyte.
8. The method for preparing the lithium-containing compound / carbon composite material according to claim 1 or 7, characterized in that: The lithium-containing compound comprises one or more of lithium nitride, lithium oxide, lithium sulfide and lithium phosphide; The chemical bond between the lithium-containing compound and the carbon substrate includes one or more of CSP-Li, C-Co-O-Li, C-Mo-N-Li, CN-Mo-Li, CO-Ni-Li, CO-Li, CN-Li, CS-Li, CP-Li, C-Co-Li and C-Mo-Li.
9. The lithium-containing compound / carbon composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the lithium-containing compound / carbon composite material according to claim 9 in lithium compensation of lithium battery positive electrode materials.
Citation Information
Patent Citations
Alkali metal fluoride / carbon composite material and preparation and application thereof
CN115117469A
Lithium ion battery based on cathode in-situ lithium supplement and preparation method thereof
CN115663310A
Metal / carbon coated lithium oxide composite positive electrode material and preparation method thereof, and positive plate and battery containing positive electrode material
CN116344763A
Cited By
Lithium ion battery negative electrode material, preparation method thereof and lithium ion battery
CN121748333A